“Your Ovaries Are Expired, Like an Old Lady” Metaphor Analysis of Saudi Arabian Women’s Descriptions of Breast Cancer: A Qualitative Study - Almegewly, Wafa Hamad; Alsoraihi, Maha Hamed (Frontiers in Psychology, 2022)
Background Assessing and understanding the language that women use to express physical, emotional, and social concerns of breast cancer experiences can often be overlooked, even though there is evidence that effective communication between cancer patients and health care providers improves quality of life. This study aims to assess the use of metaphors in conceptualizing breast cancer experience lived by Saudi Arabian women. Materials and Methods This is an interpretative phenomenological qualitative study, a purposeful sample of 18 breast cancer patients at an oncology outpatient’s clinic in Saudi Arabia were invited to engage in face-to-face interviews. Data was analyzed using Metaphor Identification Procedure (MIP). Results Four themes were constructed: dark hidden force, battling imminent death, dreaming and awakening calls, and inner and outer transformation. Conclusion Identifying metaphors may be beneficial toward improving communication between health care providers and breast cancer patients, who often experience difficulties expressing their needs.